Kelarutan dan Swelling Power Mikrokapsul β-Karoten Terenkapsulasi dalam Matriks Pati-Kitosan Terikat Silang Ion Tripolifosfat - Agnes Dyah Novitasari Lestari (Jurnal Natural, 2022)
In this study, microencapsulation of β-carotene was carried out in a mixed matrix of starch and chitosan with the addition of tripolyphosphate ions as a crosslinker (denoted as starch-chitosan/TPP). Two types of starch were used here, namely native and hydrolyzed starch. Hydrolyzed starch was prepared by acid hydrolysis using 2 M HCl. Microcapsules were synthesized by adding dropwise dispersion of β-carotene in ethanol to the aqueous mixture of starch-chitosan/TPP matrix accompanied by magnetic stirring and heating at 90ºC. The synthesized microcapsules were then tested for solubility and swelling power in aqueous media. The results showed that the solubility and swelling behavior of microcapsules were influenced by the characteristics of the constituent starch. The solubility of hydrolyzed starch-chitosan/TPP was greater than that of the native starch-chitosan/TPP. The native starch-chitosan/TPP microcapsules had a higher swelling power value than the hydrolyzed starch-chitosan/TPP.